“Occorre riflettervi ancora”. Considerazioni in margine a Fantasia e immagine di Edmund Husserl - Piana, Giovanni (Bollettino Filosofico, 2018)
The publication in Italian of Husserl’s unpublished manuscripts on the subject of the philosophy of imagination is the starting point of this paper for some general considerations on the method followed by Husserl in a phenomenological research that he personally carried out. Some doubts that may arise in the development of the investigation are touched upon, especially in relation to the problem of the notion of “Phantasm” as a mediation for the production of images of fantasy.